(3SfG HQbs - (3GdYdhj, GdehShj, GdOGQGHj, GdcTaj(B.(3, LYaQ Hf CHj ESMGb, (B1267 (3g`s
(3ChdgG (B:s
(3GdMeO ddg (B...(3a GdTjN cHjQ GdfGMjI CHj LYaQ YKeGf Hf GdSYjO bOS Gddg Gddg QhMg JhbjYG hJJejeG hUGMH GdJhbjY hgh ehdGfG GdMLI GdbGFe YLd Gddg aQLg (B...s
(3BNQgG (B:s
... (3hCHQR dfG ajg GdaSe HGSec GdCYXe GdCLd GdCcQe GdPj hVYJg GdfgGQ aCVGA hYdi Gddjd aCXde hGZaQ dfG eG JYde efG hdG fYde hGYUefG ef GdPfhH (B.s
(3JHUQI GdYfhGf (B:s
(3jYfj TQM OYGA QLH GdNGQL ef GdfGMjI GdebOSI Ydi jO GdTjN GdcHjQ CHj LYaQ eMeO Hf YKeGf Hf SYjO GdeYQha eRGQg aj HZOGO HGdTjN GdNdGfj , GdPQjYIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3eYLe GdeDdajf (B1\487s
(3GdPQjYI (B12 - 166 ( 1520)s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdCOHs